Characteristics of emergency general surgery services in Switzerland: A nationwide survey. (1st June 2022) - Quaile, O; Perrodin, S; Trippel, A; Schnüriger, B; ,
Abstract: Objective: Running emergency general surgery (EGS) services is challenging and requires significant personnel and institutional resources. In addition, increasing specialization of surgeons has made the provision of EGS services more problematic. The aim of this study was to elaborate a nationwide overview of the individual hospital organization systems of EGS services in Switzerland and to find related challenges and difficulties. Methods: Telephone based standardized survey of all Swiss hospitals with a state medical treatment contract of the Swiss Federal Office of Public Health (FOPH) including a surgical and emergency unit (ER). The telephone interviews were conducted between December 2021 and January 2022. A corresponding junior, senior consultant or attending surgeon was interviewed per hospital by one of four interviewers. Descriptive and univariate analysis was performed using SPSS Version 28. Results: A total of 72 of 79 (91.1%) surgical clinics participated in the telephone survey. There were 19 (26.4%) hospitals with <100 beds, 37 (54.2%) hospitals with 100–300 beds, 7 (9.7%) with 300–600 beds, and 7 (9–7%) with >600 beds. 57 (79.2%) hospitals have both, an ER and an intensive care unit (ICU). Eight (11.1%) hospitals have solely an intermediate care unit (IMC), 7 (9.7%) solely an ER. The average number of surgeons per hospital was proportional to the size of the hospital: 11.1±4.1 surgeons in hospitals <100 beds, 23.1±8.8 surgeons in hospitals with 100–300 beds, 29.1±10 surgeons in hospitals with 300–600 beds, and 37.7±9.4 surgeons in hospitals >600 beds. The percentage of surgical staff on EGS service per hospital was significantly higher in smaller hospitals (<100 beds), however, with a smaller number of surgeons on service per day. Regarding personal resources to run the EGS services, for hospitals with >300 beds similar person-days per month were found (159.7±24.7). Conclusion: This study elaborates and characterises for the first time EGS services in Switzerland. Different EGS systems are in place and are related to the size of the hospitals. The individual EGS systems have been discussed regarding (1) surgical expertise, (2) continuity of treating surgical teams, (3) teaching and (4) optimization of personnel hospital resources. Moreover, based on these results, recommendations have been made to optimize EGS services.